2019
DOI: 10.1101/750141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural killer cell activation by respiratory syncytial virus-specific antibodies is decreased in infants with severe respiratory infections and correlates with Fc-glycosylation

Abstract: AbstractBackgroundRespiratory syncytial virus (RSV) is a major cause of severe lower respiratory tract infections in infants and there is no vaccine available. In early life, the most important contributors to protection against infectious diseases are the innate immune system and maternal antibodies. However, the mechanisms by which antibodies can protect against RSV disease are incompletely understood, as both antibody levels and neutralizat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
17
0
1
Order By: Relevance
“…When these virus-specific antibodies are not able to completely prevent infection, as often appears to be the case, they might still be able to mitigate the development of severe disease, for example, via the recruitment and activation of (innate) immune cells through Fc-mediated interactions (for reviews, see references 11 and 20 ). We have recently shown that, in infants, the capacity of RSV-specific antibodies to activate natural killer cells might contribute to protection from severe disease ( 21 ). In contrast, these antibodies potentially also contribute to the development of severe disease, in a process referred to as antibody-dependent enhancement (ADE) of infection and/or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…When these virus-specific antibodies are not able to completely prevent infection, as often appears to be the case, they might still be able to mitigate the development of severe disease, for example, via the recruitment and activation of (innate) immune cells through Fc-mediated interactions (for reviews, see references 11 and 20 ). We have recently shown that, in infants, the capacity of RSV-specific antibodies to activate natural killer cells might contribute to protection from severe disease ( 21 ). In contrast, these antibodies potentially also contribute to the development of severe disease, in a process referred to as antibody-dependent enhancement (ADE) of infection and/or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is a major cause of severe lower respiratory tract disease, and is the leading cause for mortality in infants and the elderly [ 32 , 77 ]. Infection is characterised by airway obstruction, runny nose, shortness of breath, wheezing, hypoxia and in severe cases, pneumonia and bronchiolitis [ 78 ].…”
Section: Viral Infection Immune Dysregulationmentioning
confidence: 99%
“…The hRSV infection of both neonate and adult NK cells has recently been reported [ 233 ]. NK cells are poorly susceptible to hRSV infection, but the Ig-coating of hRSV greatly enhances the infection [ 233 ], suggesting yet again a possible role of the Fc receptors in the hRSV infection of immune cells. Moreover, hRSV-infected NK cells secrete higher amounts of IFN-γ than non-infected NK cells, while perforin secretion remains unaltered [ 233 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
“…NK cells are poorly susceptible to hRSV infection, but the Ig-coating of hRSV greatly enhances the infection [ 233 ], suggesting yet again a possible role of the Fc receptors in the hRSV infection of immune cells. Moreover, hRSV-infected NK cells secrete higher amounts of IFN-γ than non-infected NK cells, while perforin secretion remains unaltered [ 233 ]. Thus, the hRSV infection of NK cells possibly leads to a worsening of the respiratory symptoms caused by hRSV through IFN-γ-mediated pulmonary inflammation.…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%